Time for a rethink of research proposal evaluation? - WEAIRE, DENIS LAWRENCE (My University, 2007)
The processes of research proposals and evaluation have become ever more elaborate, but the system remains primitive. This paper argues for a fresh look at existing practices, with a view to developing less onerous and more efficient systems.
PUBLISHED
Keywords: Information Science; Scholarly communication; research proposals